Adverse events following immunization of combined diphtheria, whole-cell pertussis, tetanus, and hepatitis B (DPwT/HB) vaccine - Diana Mettadewi Jong; Alan R Tumbelaka; Abdul Latief (Indonesian Pediatric Society Publishing House, 2016)
Background Combined vaccine of diphtheria, whole-cell pertussis, tetanus, and hepatitis B (DPwT/HB) will reduce the number of injections to children and simplify the delivery logistics. The adverse events following immunization (AEFI) of this vaccine have to be concerned since the events may increase or decrease. Objectives To evaluate AEFI of DPwT/HB vaccine in healthy in- fants. Methods A descriptive prospective study of AEFI of three doses of DPwT/HB vaccine was performed on 74 healthy infants aged two to six months at the Department of Child Health, Cipto Mangunkusumo Hospital, from July 2000 to March 2001. Results Out of 74 infants, 68 received two doses and 67 completed the study with a total of 209 doses. Of 209 doses, adverse events were reported following 126 doses (60.3%), consisted of systemic (60.3%) and local reactions (9.5%). The three most frequent AEFI iwere mild fever (44.5%), high fever (15.7%), irritability (31.5%). Most AEFI were coincidental (51.1%), occurred after more than 72 hours (31.4%) and lasted less than 24 hours (17.7%). Sys- temic reactions were mostly found in 4-month-old infants (33.3%), while local reactions in 2-, 3-, and 5-month-old infants (25%), respectively. Conclusion Most AEFI were coincidental and resolved without any complication